ERRATUM TO: KNOWLEDGE, ATTITUDE, AND PRACTICE OF COUGH ETIQUETTE IN PATIENTS WITH TUBERCULOSIS IN THE COMMUNITY HEALTH CENTERS - Desy Indra Yani; Yayat Fajar Hidayat; Afif Amir Amrullah (Belitung Nursing Journal, 2020)
After the publication of the article (Yani et al., 2018), it has been brought to our attention that the wrong title was used on the initial publication. The correct title of this article is “Knowledge, attitude, and practice of cough etiquette in patients with tuberculosis in the community health centers.” The original version of the article has been updated to reflect this. The reference and layout formats in this article have also been updated. The publisher apologizes for the errors. The corrected article can be seen at https://doi.org/10.33546/bnj.509